Sliding mode-based DTC-SVM control of permanent magnet synchronous motors for plug-in electric and hybrid vehicles. (1st January 2011) - Fu, Hong; Chen, Yaobin; Tian, Guangyu; Chen, Quanshi
This paper presents a sliding mode controller design for a permanent magnet synchronous motor used in an integrated powertrain for plug-in electric and hybrid vehicles. In order to adapt to complicated driving environment and improve the robustness of the system, a sliding mode-based torque controller is developed. At the same time, a sliding mode speed controller is also proposed to meet the need of gear shift of the integrated powertrain. The stability and robustness of the proposed controllers are analysed. Computer simulations are performed to verify the effectiveness of the proposed control system. The simulation results illustrate that fast response and small ripples are achieved using the proposed control scheme. It is also shown that the control system is robust against load variations, measurement errors and parameter uncertainty. In addition, the transition during shift is smooth. Therefore, the proposed control scheme is suitable for control of the propulsion motor for plug-in electric and hybrid vehicles.